Smoking Decisions: Altered Reinforcement Learning Signals Induced by Nicotine State. Issue 2 (30th June 2018) - Baker, Travis E; Zeighami, Yashar; Dagher, Alain; Holroyd, Clay B
Abstract: Introduction: Alterations in dopamine signaling play a key role in reinforcement learning and nicotine addiction, but the relationship between these two processes has not been well characterized. We investigated this relationship in young adult smokers using a combination of behavioral and computational measures of reinforcement learning. Methods: We asked moderately dependent smokers to engage in a reinforcement learning task three times: smoking as usual, smoking abstinence, and cigarette consumption. Participants' trial-to-trial training choices were modeled using a reinforcement learning model that calculates separate learning rates associated with positive and negative prediction errors. Results: We found that learning from positive prediction error signals is reduced during smoking abstinence and enhanced following cigarette consumption. By contrast, learning from negative prediction error signals was enhanced during smoking abstinence and reduced following cigarette consumption. Finally, when tested with novel pairs of stimuli, participants were relatively better at selecting the positive feedback predicting stimuli than avoiding the negative feedback predicting stimuli during the smoking as usual session, a pattern that reversed following cigarette consumption. Conclusions: These findings provide a specific computational account of altered reinforcement learning induced by smoking state (abstinence and consumption) and may represent a unique target for treatment of nicotine addiction. Implications: This study illustrates the potential of computational psychiatry for understanding reinforcement learning deficits associated with substance use disorders in general and nicotine addiction in particular. We found that learning from positive prediction error signals is reduced during smoking abstinence and enhanced following cigarette consumption. By contrast, learning from negative prediction error signals was enhanced during smoking abstinence and reduced following cigarette consumption. By highlighting important computational differences between three states of smoking, these findings hold out promise for integrating experimental, computational, and theoretical analyses of decision-making function together with research on addiction-related disorders.